'Le Crete 1' and 'Le Crete 2': two newly patented Seiridium cardinale canker‐resistant cultivars of Cupressus sempervirens. Issue 3 (21st December 2012) - Danti, R.; Di Lonardo, V.; Pecchioli, A.; Della Rocca, G.; Woodward, S.
Summary In the Mediterranean area, common cypress (Cupressus sempervirens) has traditionally been used as a multipurpose tree, for its symbolic and ornamental role, for its valuable timber, as well as for windbreaks and soil protection. The epidemic spread of the Seiridium cardinale canker has limited the use of this tree since the 1970s, inducing researchers to develop a breeding programme of cypress aimed at selecting canker‐resistant lines for different uses and to support a flourishing trade of cypress plants. 'Le Crete 1' and 'Le Crete 2' described here are two new canker‐resistant C. sempervirens varieties patented in 2010, selected through a 13‐year assessment of their response to artificial inoculations and growth traits. Both are characterized by a rapid growth and by a columnar and fastigiated habit that confers them a notable ornamental effect. Preliminary observations showed also that both tend to produce yearly few microsporophylls and little pollen. 'Le Crete 2' was also selected for the high growth rate it maintained on heavy, clayey soils.